Slavery's Exiles : The Story of the American Maroons - Diouf, Sylviane A. (Sylviane Anna), 1952- (Book collections on Project MUSE., 2014)
"Over more than two centuries men, women, and children escaped from slavery to make the Southern wilderness their home. They hid in the mountains of Virginia and the low swamps of South Carolina; they stayed in the neighborhood or paddled their way to secluded places; they buried themselves underground or built comfortable settlements. Known as maroons, they lived on their own or set up communities in swamps or other areas where they were not likely to be discovered. Although well-known, feared, celebrated or demonized at the time, the maroons whose stories are the subject of this book have been forgotten, overlooked by academic research that has focused on the Caribbean and Latin America. Who the American maroons were, what led them to choose this way of life over alternatives, what forms of marronage they created, what their individual and collective lives were like, how they organized themselves to survive, and how their particular story fits into the larger narrative of slave resistance are questions that this book seeks to answer. To survive, the American maroons reinvented themselves, defied slave society, enforced their own definition of freedom and dared create their own alternative to what the country had delineated as being black men and women's proper place. Audacious, self-confident, autonomous, sometimes self-sufficient, always self-governing; their very existence was a repudiation of the basic tenets of slavery. Sylviane A. Diouf is an award-winning historian specializing in the history of the African Diaspora, African Muslims, the slave trade and slavery. She is the author of Servants of Allah: African Muslims Enslaved in the Americas (NYU Press, 2013) and Dreams of Africa in Alabama: The Slave Ship Clotilda and the Story of the Last Africans Brought to America, and the editor of Fighting the Slave Trade: West African Strategies."--